1996
DOI: 10.1111/j.1526-100x.1996.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Restored and Mature Bottomland Hardwood Forests of Southwestern Kentucky

Abstract: We evaluated 50‐year‐old bottomland forests in southwestern Kentucky restored from agriculture by planting and natural regeneration in terms of their development toward mature forests. We described and compared the structure and composition of the plant communities of three stands of each type (planted, naturally regenerated, and mature). Increment cores were analyzed to reconstruct developmental trends. Future trends were predicted from analyses of the midstory and understory composition. Both planting and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 18 publications
4
20
0
1
Order By: Relevance
“…In tropical forests, DeWalt et al (2000) reported significantly lower liana density and species richness in forests older than 70 years; however, they also found that basal area of vines remained the same as lianas increased in size in mature forests. Moreover, Shear et al (1996) reported that poison ivy (Rhus radicans L.), the dominant liana in bottomland forests in Kentucky, was much more abundant in mature forests than in 50-year-old restored forests where native bottomland tree species had been planted.…”
Section: Introductionmentioning
confidence: 98%
“…In tropical forests, DeWalt et al (2000) reported significantly lower liana density and species richness in forests older than 70 years; however, they also found that basal area of vines remained the same as lianas increased in size in mature forests. Moreover, Shear et al (1996) reported that poison ivy (Rhus radicans L.), the dominant liana in bottomland forests in Kentucky, was much more abundant in mature forests than in 50-year-old restored forests where native bottomland tree species had been planted.…”
Section: Introductionmentioning
confidence: 98%
“…Allen (1997) found that large, relatively isolated fields had much lower densities of woody colonizers than long, narrow fields or especially fields with mature forest on more than one edge (Shear et al, 1996;Allen, 1997). Nevertheless, we found that even narrow strips of vegetation along ditch banks can provide seed, and noticeable dispersal occurs even when sources are more than 0.5 km distant (Fig.…”
Section: Passive To Active Comparisonmentioning
confidence: 97%
“…Short-term monitoring is concerned with determining the performance of the project following installation. It can also be used to detect responses that call for management action ( Shear et al (1996) allows retention of some project resources for the postconstruction phase to allow adaptive management. The temporal and spatial frequency of the monitoring should largely be determined prior to installation.…”
Section: Monitoringmentioning
confidence: 99%